PENGARUH KETERLIBATAN AYAH DALAM PENGASUHAN TERHADAP SIKAP MANDIRI ANAK DI RA AL IKHLAS KAMPUNG BANGUN - Reyhan Al Fitri Melyana; Mavianti Mavianti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to determine the involvement of fathers in parenting towards children's independent attitudes in RA Al Ikhlas Kampung Bangun. The hypothesis in this study is that there is a significant influence between the involvement of fathers in parenting and the child's independent attitude. The sample in this study consisted of 50 parents who had children aged 4-6 years. This type of research is quantitative research with data collection methods using questionnaires. The analysis technique used is simple linear regression analysis. The results showed that there was an influence between the involvement of fathers in parenting on children's independent attitudes, this was evidenced by a regression coefficient of 0.646 with a significant 0.000 which was lower than alpha 0.05 with a beta coefficient value of 0.571. In other words every one-unit increase in the father's level of involvement in parenting will result in an increase of 0.646 in the child's independent attitude, while considering that this relationship is positive and linear. Thus showing that Ha was accepted and Ho was rejected. It can be concluded that there is an influence of father's involvement in parenting and plays an important role in shaping children's independent attitudes in the RA Al Ikhlas Kampung Bangun environment.